Light and heavy touch reduces postural sway and modifies axial tone in Parkinson’s disease - Franzén, Erika (2012)
BACKGROUND: Light touch with a stable object reduces postural sway by increasing axial postural tone in healthy subjects. However, it is unknown whether subjects with Parkinson’s disease (PD), who have more postural sway and higher axial postural tone than healthy subjects, can benefit from haptic touch. OBJECTIVE: To investigate the effect of light and heavy touch on postural stability and hip tone in subjects with PD. METHODS: Fourteen subjects with mid-stage PD, and 14 healthy control subjects were evaluated during quiet standing with eyes closed with their arms: 1) crossed, 2) lightly touching a fixed rigid bar in front of them and 3) firmly gripping the bar. Postural sway was measured with a forceplate and axial hip tone was quantified using a unique device that measures the resistance of the hips to yaw rotation while maintaining active stance. RESULTS: Subjects with PD significantly decreased their postural sway with light or heavy touch (p<0.001 vs. arms crossed), similarly as control subjects. Without touch, hip tone was larger in PD subjects. With touch, however, tone values were similar in both groups. This change in hip tone with touch was highly correlated with the initial amount of tone (PD: r=− 0.72 to −0.95 and controls: r=−0.74 to−0.85). CONCLUSIONS: We showed, for the first time, that subjects with PD benefit from touch similarly to control subjects and that despite higher axial postural tone, PD subjects are able to modulate their tone with touch. Future studies should investigate the complex relationship between touch and postural tone.